Study protocol: parents as pain management in Swedish neonatal care - SWEpap, a multi-center randomized controlled trial - Emma Olsson; Martina Carlsen Misic; Randi Dovland Andersen; Jenny Ericson; Mats Eriksson; Ylva Thernström Blomqvist; Alexandra Ullsten (BMC, 2020)
Abstract Background During the first period of life, critically ill as well as healthy newborn infants experience recurrent painful procedures. Parents are a valuable but often overlooked resource in procedural pain management in newborns. Interventions to improve parents' knowledge and involvement in infants' pain management are essential to implement in the care of the newborn infant. Neonatal pain research has studied a range of non-pharmacological pain alleviating strategies during painful procedures, yet, regarding combined multisensorial parent-driven non-pharmacological pain management, research is still lacking. Methods/design A multi-center randomized controlled trial (RCT) with three parallel groups with the allocation ratio 1:1:1 is planned. The RCT "Parents as pain management in Swedish neonatal care - SWEpap", will investigate the efficacy of combined pain management with skin-to-skin contact, breastfeeding and live parental lullaby singing compared with standard pain care initiated by health care professionals, during routine metabolic screening of newborn infants (PKU-test). Discussion Parental involvement in neonatal pain management enables a range of comforting parental interventions such as skin-to-skin contact, breastfeeding, rocking and soothing vocalizations. To date, few studies have been published examining the efficacy of combined multisensorial parent-driven interventions. So far, research shows that the use of combined parent-driven pain management such as skin-to-skin contact and breastfeeding, is more effective in reducing behavioral responses to pain in infants, than using the pain-relieving interventions alone. Combined parental soothing behaviors that provide rhythmic (holding/rocking/vocalizing) or orogustatory/orotactile (feeding/pacifying) stimulation that keep the parent close to the infant, are more effective in a painful context. In the SWEpap study we also include parental live lullaby singing, which is an unexplored but promising biopsychosocial, multimodal and multisensory pain alleviating adjuvant, especially in combination with skin-to-skin contact and breastfeeding. Trial registration ClinicalTrials.gov ( NCT04341194 ) 10 April 2020.